Implementation of Islamic Religious Education Learning in Inclusive Classes in Elementary Schools: Implementasi Pembelajaran Pendidikan Agama Islam Pada Kelas Inklusi Di Sekolah Dasar - Bayu Dwi Cahyono; Anita Puji Astutik (Universitas Muhammadiyah Sidoarjo, 2022)
Education plays an important role for Indonesia. A good education will have a good influence on the next generation. But vice versa, if education is bad then of course this nation's generation will not have quality. Theoretically, this research can add to the treasury of new knowledge, especially regarding the implementation of Islamic religious education in inclusive classes. This type of research is qualitative research, which is a study that seeks to reveal the symptoms holistically. This means that this research is carried out directly in the field (research place). The teaching and learning process of Islamic Religious Education in inclusive classes sometimes does not run smoothly. The main obstacle when studying Islamic Religious Education is the physical ability and understanding of students in the ABK category which is different from students in general. So that students with the ABK category must get special assistance that will be carried out by special assistant teachers.